Randomised controlled trial of a psychiatric consultation model for treatment of common mental disorder in the occupational health setting - de Jong Fransina J; Meeuwissen Jolanda AC; van der Feltz-Cornelis Christina M; Hoedeman Rob; Elfeddali Iman (BMC, 2007)
Abstract Background Common mental disorders are the most prevalent of all mental disorders, with the highest burden in terms of work absenteeism and utilization of health care services. Evidence-based treatments are available, but recognition and treatment could be improved, especially in the occupational health setting. The situation in this setting has recently changed in the Netherlands because of new legislation, which has resulted in reduced sickness absence. Severe mental disorder has now become one of the main causes of work absenteeism. Occupational physicians (OPs) are expected to take an active role in diagnosis and treatment, and seem to be in need of support for a new approach to handle cases of more complex mental disorders. Psychiatric consultation can be a collaborative care model to achieve this. Methods/design This is a two-armed cluster-randomized clinical trial, with randomization among OPs. Forty OPs in two big companies providing medical care for multiple companies will be randomized to either the intervention group, i.e. psychiatric consultation embedded in a training programme, or the control group, i.e. only training aimed at recognition and providing Care As Usual. 60 patients will be included who have been absent from work for 6-52 weeks and who, after screening and a MINI interview, are diagnosed with depressive disorder, anxiety disorder or somatoform disorder based on DSM-IV criteria. Baseline measurements and follow up measurements (at 3 months and 6 months) will be assessed with questionnaires and an interview. The primary outcome measure is level of general functioning according to the SF-20. Secondary measures are severity of the mental disorder according to the PHQ and the SCL-90, quality of life (EQ-D5), measures of Return To Work and cost-effectiveness of the treatment assessed with the TiC-P. Process measures will be adherence to the treatment plan and assessment of the treatment provided by the Psychiatric Consultant (PC) in both groups. Discussion In the current study, a psychiatric consultation model that has already proved to be effective in the primary care setting, and aimed to enhance evidence-based care for patients with work absenteeism and common mental disorder will be evaluated for its efficacy and cost-effectiveness in the occupational health setting.